Holding it together: Coping with vicarious trauma in sport - Day, M. C.; Bond, K.; Smith, B. (Psychology of Sport and Exercise, 2013)
Objectives: Vicarious trauma refers to the negative effects that may be experienced after witnessing trauma (such as actual or threatened injury) in others. This study aims to examine vicarious trauma in sports coaches by drawing on the experiences of two trampoline coaches who have witnessed a serious athletic injury. In particular, this study focuses on how these coaches have responded to and coped with this traumatic event. Design: The study draws on data from thematic, semi-structured, life history interviews that focus on the occurrence of one particular sports accident witnessed by both coaches. Method: Multiple interviews were conducted in which participants were invited to recall the accident, their own responses to the accident, and the coping strategies employed. Interviews were analyzed using a holistic-content analysis in which thematic similarities and differences between the narratives emerged. Results: There were three main themes that emerged, these were the need to make meaning following trauma, re-experiencing trauma, and acceptance and avoidance coping. Participants demonstrated the individual nature of coping with trauma. While one participant avoided the trauma by minimizing the events, blocking her emotions and giving support to others; the second participant showed acceptance of the trauma, was highly emotional, and received support from others. Conclusions: This study demonstrates the difficulties that may be faced by coaches following vicarious trauma. Although each coach presents different experiences and coping strategies they provide some indications of the level and type of support that may be required after witnessing athletic injury.